Smart Home Electricity Usage Monitoring and Controlling System using Raspberry Pi - Gerry Italiano Wowiling (Prodi Teknik Mesin, 2022)
Almost all household appliances nowadays using electricity as power, increasing the use of electricity in each household. Usually human use electricity excessively and uncontrollable, leading to overpayment of electricity each time and decreasing the electricity resource itself, where saving energy including electricity is necessary. A smart system that can monitor and control the usage of electricity based on need become one of the best approach to tackle the problem of excessive and uncontrollable usage of electricity. In this paper, we create a smart system that can monitor and control electricity usage in household using Raspberry Pi and Current Transformer Sensor to process and detect electricity data, relay to control and build a web application as interface using PHP and MYQL database for human to configure and setting the usage of household appliances in their own. This smart system also give report and notification to the user that can be configured daily, weekly, or monthly so that the user know how much electricity they has been used. They information we provide includes implementation of raspberry pi and current transformer sensor, designing and building web application interface, data and result of the smart system.